Analysis of ways to reduce CO2 emissions by vehicles - Mayboroda, О.В.; Kalenov, Г.К.; Mustayap, М.Б. (Eurasian Journal of Applied Engineering and Technology (EJAET), 2022)
The article considers possible ways to reduce CO2 emissions. CO2 emissions are reduced in proportion to the reduction in operational fuel consumption. The use of electric vehicles does not reset CO2 emissions, but only reduces them. Electricity is mainly generated by thermal power plants. By reducing electric vehicle power consumption, the authors reduce CO2 emissions from thermal power plants. The article considers the following ways to reduce the operational fuel consumption of cars and electric power by electric vehicles: limiting the excess power of the engines of cars and electric vehicles; the use of hybrid power plants; the use of economical algorithms for regulating the speed of cars with an internal combustion engine and electric vehicles. The article focuses on the need to develop an economical algorithm for speed control for electric vehicles. The article shows that the existing designs of automatic transmissions and the designs of most electric vehicles do not allow the use of rolling motion to reduce the operational consumption of fuel (electricity). The article presents the necessity of maintaining the permitted speed of passenger cars on motorways at the level of 110 km/h. The article considers the influence of the slipperiness of the road surface and the intensity of traffic on the average and maximum speeds of the traffic flow. Flexible regulation of the maximum speed and limitation of overtaking increase the driving time of the car at a constant speed, which reduces fuel consumption.